THE ROLE OF AMP-ACTIVATED PROTEIN KINASE IN NEURODEGENERATION IN PARKINSON’S DISEASE - Jovanović Tucović, Maja; Marković, Ivanka (Medicinski podmladak, 2019)
Parkinson’s disease (PD) is defined as chronic neurodegenerative disorder with a gradual demise of dopaminergic (DA) neurons in substantia nigra pars compacta. Although molecular mechanisms of DA neurons’ degeneration are still insufficiently understood, different studies based on animal, toxic and genetic models, as well as post-mortem brain tissue analyses revealed several common features of neuronal death in SN: mitochondrial dysfunction, increased ROS production and impaired proteostasis. Each of these mechanisms might be, at least in part, related to adenosine monophosphate activated protein kinase (AMPK). AMPK is a major intracellular energy sensor. It can be activated by different types of metabolic stress, mediated by at least three different kinases LKB1, CAMKKβ and TAK1, in conditions of decreased cellular ATP and/or increased Ca2+ level. Once activated, AMPK promotes catabolic pathways, inhibits mTORC1, and stimulates autophagy, mitochondrial biogenesis and turnover. Different studies revealed a growing body of evidence suggesting an important role of AMPK in PD. Many of them have documented protective effect of AMPK activation in different PD models by facilitating mitochondrial quality control, enhancing autophagic clearance of defective mitochondria and protein aggregates. However, some studies have shown the detrimental effect of AMPK activation in DA neurons in advanced stages of neuronal damage, where prolonged activation could inhibit protein synthesis and impair synaptic integrity and plasticity. In this review, we will try to summarize the literature data regarding the role of AMPK in PD pathogenesis. Keywords: AMPK, Parkinson’s disease, mitochondria, autophagy